2020
DOI: 10.1002/jmv.25690
|View full text |Cite
|
Sign up to set email alerts
|

Induction of cross‐neutralizing antibodies by sequential immunization with heterologous papillomavirus L1VLPs and its implications for HPV prophylactic vaccines

Abstract: Sequential immunization with antigens from different strains of HIV‐1, influenza viruses or dengue viruses induced cross‐neutralizing antibodies and enhanced the antibody responses against previous antigens. The characteristics of neutralizing antibodies induced by sequential immunization with different types of human papillomavirus (HPV) L1 virus‐like particles (L1VLPs) are unclear. In this study, mice were primed with one or two types (HPV‐16 or HPV16/18) of L1VLPs, then boosted sequentially with HPV6/18/45/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 60 publications
0
3
0
Order By: Relevance
“…Studies on influenza virus, HIV and HPV, etc . reported that sequential immunization with similar antigens can enhance conserved epitope‐dependent humoral and cellular immune responses 51–53 . Therefore, in this study, mice were sequentially immunized with 2RBD‐Fc, 2dRBD‐Fc, and 2omRBD‐Fc (SI group), and the characteristics of the induced humoral and cellular immune responses were assessed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies on influenza virus, HIV and HPV, etc . reported that sequential immunization with similar antigens can enhance conserved epitope‐dependent humoral and cellular immune responses 51–53 . Therefore, in this study, mice were sequentially immunized with 2RBD‐Fc, 2dRBD‐Fc, and 2omRBD‐Fc (SI group), and the characteristics of the induced humoral and cellular immune responses were assessed.…”
Section: Discussionmentioning
confidence: 99%
“…reported that sequential immunization with similar antigens can enhance conserved epitopedependent humoral and cellular immune responses. [51][52][53] Therefore, F I G U R E 4 Sera antibody responses elicited by sequential immunization with DNA vaccines derived from Wuhan-Hu-1, delta and omicron VOC. Schematic diagram of immunization schedule was shown in (A).…”
Section: F I G U R E 4 (See Caption On Next Page)mentioning
confidence: 99%
“…Sequential immunization has been used to develop vaccines against highly variable viruses, such as influenza viruses [ 32 , 33 ] and human papillomaviruses [ 34 ]. This approach has also been used for HIV-1 vaccine development, but no significant improvements have been achieved by simply using the unrelated Env immunogens from different virus strains [ 35 , 36 , 37 ].…”
Section: Introductionmentioning
confidence: 99%